Analisis Pesebaran Penularan Virus Corona di Provinsi Jawa Tengah Menggunakan Metode K-Means Clustering - Darmansah Darmansah Darmansah; Ni Wayan Wardani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Currently the corona virus or Covid-19 has developed rapidly and it has been reported that almost all over the world have been exposed to the transmission of the corona virus. Covid-19 has claimed thousands of human lives in China in just 3 months. This virus has even spread to other countries such as Italy, Iran, South Korea, England, Japan, America, Germany, and even in Indonesia. One of the provinces in Indonesia that has contracted the corona virus is the province of Central Java (Prov. Central Java). This corona virus has spread in various districts and cities in Central Jawah. There are 35 districts / cities in Central Java that have contracted the corona virus. To make it easier for the Central Java regional government to take measures to prevent the spread of the corona virus, it is necessary for researchers to determine the level of spread of the corona virus which is divided into three clusters. The first cluster is C0 with a low category, C1 with a medium category and C2 with a high spread category. In the analysis of the spread of the corona virus, the researchers used data mining methods and the K-Means Clustering algorithm to classify the distribution data. Then in data processing researchers use the Rapidminer Studio 7.6 application. From the results of the study, it was found that C0 there were 18 cities / districts, C1 there were 1 city / regency and C2 there were 16 cities / districts where the spread of the corona virus was in Central Java province.